UFOs: Above the Law, True Encounters with Law Enforcement by James Bouck and Frank Soriano - Maccabee, Bruce (Journal of Scientific Exploration, 2012)
No man is above the law, so they say. But what about non-man, that is non-humans or aliens, be they extraterrestrial or interdimensional or whatever? Are they “above the law?” According to this book they are, literally, as when a police officer looks up and sees a UFO that appears to be an AFC (alien flying craft) above him. Before you say “That is silly because there are no AFC so they couldn’t appear ‘above the law,’” you should read this book and see how many times law enforcement personnel have reported UFOs that seem to be AFCs. According to Edward Condon, director of the so-called “scientific study of UFOs” carried out at the University of Colorado at the request of the Air Force in the latter 1960s, only poor observers report UFOs. If this were true one would expect that UFO reports from police would be as scarce as hair on a billiard ball because law enforcement officers are trained to be good observers. However, as demonstrated in this book, police are as likely to report UFO sightings as are people in other jobs and professions.